2012
DOI: 10.1007/s00253-011-3746-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen supply in Bacillus thuringiensis fermentations: bringing new insights on their impact on sporulation and δ-endotoxin production

Abstract: The growth kinetics, sporulation, and toxicity of Bacillus thuringiensis var. israelensis were evaluated through the analysis of batch cultures with different dissolved oxygen (DO) profiles. Firstly, DO was maintained constant at 5%, 20%, or 50% throughout fermentation in order to identify the most suitable one to improve the main process parameters. Higher biomass concentration, cell productivity, and cell yield based on glucose were obtained with 50% DO. The higher aeration level also resulted in higher spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 38 publications
0
12
0
4
Order By: Relevance
“…There are numerous reports that a high DOT level has a positive effect on spore production of Bacillus spp. [20][21][22]. The higher the oxygen supply is, especially K L a, the higher the spore productivity [21,23].…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous reports that a high DOT level has a positive effect on spore production of Bacillus spp. [20][21][22]. The higher the oxygen supply is, especially K L a, the higher the spore productivity [21,23].…”
Section: Discussionmentioning
confidence: 99%
“…We can see that culture media ranging from 10 to 40 g · L −1 of glucose (disregarding the yeast extract that can be used as a carbon source, varying from 3 to 10 g · L −1 ) results in low biomass, even applying a statistical experimental design or using response surface to the components of the culture medium. Efforts to improve metabolism through oxygenation have led to a small increase in biomass 17 by maintaining a high oxygenation of at least 50%, which improves cellular metabolism and results in a slight increase in biomass of 2.4 g · L −1 , although this increases the cost on a large scale. However, it is important to emphasize that high oxygenation during sporulation decreased toxicity, and when low oxygenation is applied during the sporulation phase, the toxicity increases considerably, although the investment in nutrients is very high at 30 g · L −1 of glucose and 12 g · L −1 yeast extract.…”
Section: Discussionmentioning
confidence: 99%
“…More recent experiments report that under O 2 limitation, spore production of B. thuringiensis (a species genetically close to B. cereus) was lower than in cultures with O 2 (Foda et al, 1985;Avignone-Rossa et al, 1992;Finlay et al, 2002). Likewise, Boniolo and coworkers (Boniolo et al, 2012) showed that interrupting the oxygen supply immediately after the end of the exponential growth phase leads to a lower spore production in B. thuringiensis var israelensis (IP-82). In addition, another study established that carrying out one non-aeration period followed by a moderate oxygenation period during the sporulation phase resulted in higher sporulation of B. thuringiensis H14 (Sarrafzadeh and Navarro, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In B. cereus and Bacillus subtilis, the effect of temperature and nutrient conditions on spore resistance to heat, UV and chemicals and germination has been extensively studied (Melly et al, 2002;Faille et al, 2007;Gounina-Allouane et al, 2008;Planchon et al, 2011). Few studies on the effect of anaerobiosis on sporulation of the B. cereus group have been published except the effect of oxygen on the sporulation capacity of B. thuringiensis but spore properties were not studied (Avignone-Rossa et al, 1992;Finlay et al, 2002;Boniolo et al, 2012). Most studies on sporulation in anaerobic condition were performed with the anaerobic clostridia species (Paredes et al, 2005).…”
Section: Introductionmentioning
confidence: 99%